Improvement model framework of urban agriculture program in Malaysia: PLS-SEM analysis - Yusuf, Munifah Siti Amira; Man, Norsida; Haris, Nur Bahiah Mohamed; Ismail, Ismi Arif; Yee, Siaw Shin; Abu Bakar, Tengku Halimatun Sa’adiah T (ResearchersLinks, 2024)
The Malaysian government has introduced the Urban Agriculture Program to improve the performance of urban and rural agriculture in Malaysia. The Urban Agriculture Program was implemented by the Department of Agriculture (DOA), Malaysia in 2010. Such agricultural extension programs may significantly affect the effectiveness of adopting urban agriculture practices, which eventually help the participants with better living standards and productivity. This study aims to evaluate the effectiveness of urban agriculture programs. Primary data was collected from 230 urban agriculture program participants registered under the DOA Malaysia. The data was analysed using the PLS-SEM analysis method with the help of SMART-PLS software version 3.0. Findings revealed a positive association between all CIPP factors and Effectiveness. These findings showed that the DOA should prioritise process and product as the agriculture extension provider (stakeholders). This study suggests that policymakers should improve the implementation of urban agriculture programs in context, input, process, and product at a community level to improve food security and nutrition by 2030.